2019
DOI: 10.1038/s41419-019-1632-z
|View full text |Cite
|
Sign up to set email alerts
|

MeHg-induced autophagy via JNK/Vps34 complex pathway promotes autophagosome accumulation and neuronal cell death

Abstract: Methylmercury (MeHg), an environmental toxin, may specifically cause neurological disorders. Recent studies have reported that autophagy can be induced by metals and be involved in metal cytotoxicity. However, the role of autophagy in MeHg-induced neurotoxicity remains unknown. Here, we demonstrate that MeHg induces mTOR-independent autophagy through JNK/Vps34 complex pathway, which further promotes autophagosome accumulation and neuronal cell death. In addition to cell death, MeHg increased LC3-II expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Once the active ULK complex is recruited to the initiation site, autophagy proceeds to the next stage, i.e., the formation of autophagosomes. It has been shown that the Beclin1-VPS34-Atg14L complex is critical to the formation of autophagosomes [84]. Activated ULK1 phosphorylates Beclin1 at Ser15 and ATG14 at Ser29.…”
Section: The Canonical Role Of Ulk1mentioning
confidence: 99%
“…Once the active ULK complex is recruited to the initiation site, autophagy proceeds to the next stage, i.e., the formation of autophagosomes. It has been shown that the Beclin1-VPS34-Atg14L complex is critical to the formation of autophagosomes [84]. Activated ULK1 phosphorylates Beclin1 at Ser15 and ATG14 at Ser29.…”
Section: The Canonical Role Of Ulk1mentioning
confidence: 99%
“…One possible explanation for this finding could be that exposure to MeHg-Cys inhibits or causes degradation of the autophagic machinery. Some previous studies, using in vitro and in vivo models, reported a reduction in autophagy following exposure to MeHg [ 43 , 44 ], while other studies have shown that exposure to low doses of MeHg enhances autophagy [ 45 ]. These reported differences may be due to variations among the cell types studied, differences in the concentrations of MeHg used for the study, and the exposure time for each study.…”
Section: Discussionmentioning
confidence: 99%
“…MeHg affected lysosomal permeability as well. All of which resulted in MeHg induced cell death [ 67 ].…”
Section: Methodsmentioning
confidence: 99%